THE STRATEGY IN DEVELOPING PUBLIC TRUST OF TAXPAYERS’ COMPLIANCE IN SOUTH SULAWESI PROVINCE - Mohamad Thahir Haning; Hasniati Hamzah; Mashuri H Tahili (Magister Ilmu Administrasi Publik, 2019)
The reduced level of tax compliance in Makassar as the capital of South Sulawesi, Indonesia in 2014 to 2016 significantly became an important basis for evaluating the accountability and transparency of tax service performance. This study aims to determine the level of compliance and determinants of tax compliance in three administrative regions of South Sulawesi that represent urban and rural areas, namely, Makassar Selatan, Maros, and Palopo City through a slippery framework. Based on two concepts of economics and public administration for implementing the sliperry slope tax framework, this study then discusses coordination and trust when implementing relationships. Using a qualitative methodology, this study processed and tested the questionnaire through ANOVA to find out the results of differences in tax compliance levels in three administrative regions of South Sulawesi. This study discusses and refutes findings in previous studies. On the one hand accountability and transparancy of tax services is important to increase taxpayer awareness. This at the same time rejects other research perspectives that explain the application of coercion and persuasion to tax policies that will increase public confidence and increase taxpayer awareness. The results also showed that there were no significant differences in respondents' perceptions about the role of power and the dimensions of trust in developing public trust. The dimensions of power and trust are identified as vital to increasing the trust and compliance of taxpayers. This study recommends the need to adopt a slippery slope framework in growing and increasing the trust of taxpayers, which is important for higher taxpayer compliance in South Sulawesi Province.